Characterization of native strains of Azotobacter spp. and its effect on growth of Lycopersicon esculentum Mill. “tomato” in Lambayeque - Escobar, Cynthia (2011)
The objective of this research was characterize and determine the effect of native strains of Azotobacter spp. on the vegetative growth of Lycopersicon esculentum Mill. "Tomato" as an alternative to the indiscriminate use of chemical fertilizers. Samples were taken from roots and rhizosphere soil of vegetables from which dilutions (10-4) in Ashby-sucrose broth and incubated at 30 °C to observe a yellow color, turbidity and surface film. The genus Azotobacter was identified in mineral agar without nitrogen and Ashby-benzoate, obtaining 96 strains with a yield of 7.10 to 57.99 mgL-1 indoleacetic acid, 0.13 to 1.64 mgL-1 of fixed nitrogen as ammonium and up to 1.61% efficiency in the solubilization of phosphate Bayovar rock. It obtained a cell suspension (108) of each of the four strains with the highest values and inoculated independently and in consortium, as well as a combination with 50% urea-100 % phosphate rock in the rhizosphere of Rio Grande tomato, in a completely randomized design. The entire native strains increased height, root volume, total dry matter, shoot and root, compared with absolute control.